2019
DOI: 10.1142/s1464333219500030
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Monetary-Based Benefit-Sharing as a Mechanism to Improve Local Human Development and its Importance for Impact Assessment of Hydropower Plants in Brazil

Abstract: Although hydropower companies and governments have promoted monetary-based Benefit-Sharing Mechanisms alone as a vector of local development for flooded municipalities, it is not possible to identify this evidence in the scientific literature. The present work investigates the quantitative influence of Financial Compensation on Human Development Indexes (HDI) in flooded municipalities over 2000–2010. The econometric analysis shows that there are no statistically significant results related to the quantities of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 48 publications
1
12
0
2
Order By: Relevance
“…Dombrowsky et al [22] and Wang [13] argue that benefit sharing schemes should move beyond compensation and hence encourage social and economic gains for affected populations that have already been compensated for their losses. Furthermore, Pulice et al [23], based on the Brazilian experience, concur with Dombrowsky et al [22], whose research is based in Africa´s Great Lakes region, when they assert that monetary compensation as a benefit sharing mechanism is not a key to promoting the development of a region. In this context, there is a debate on the conceptualisation of the methods for distributing benefits, wherein it is argued that there may be different types of strategies from financial compensation to social issue management, including conflict resolution and negotiation management.…”
Section: Theoretical Frameworkmentioning
confidence: 90%
See 2 more Smart Citations
“…Dombrowsky et al [22] and Wang [13] argue that benefit sharing schemes should move beyond compensation and hence encourage social and economic gains for affected populations that have already been compensated for their losses. Furthermore, Pulice et al [23], based on the Brazilian experience, concur with Dombrowsky et al [22], whose research is based in Africa´s Great Lakes region, when they assert that monetary compensation as a benefit sharing mechanism is not a key to promoting the development of a region. In this context, there is a debate on the conceptualisation of the methods for distributing benefits, wherein it is argued that there may be different types of strategies from financial compensation to social issue management, including conflict resolution and negotiation management.…”
Section: Theoretical Frameworkmentioning
confidence: 90%
“…From the scientific literature, several studies have shown from real experiences of the hydroelectric sector important results [19][20][21], which have allowed them to raise significant contributions towards the optimisation of the mechanisms of distribution of the shared benefit. Because of the scarcity of literature that focuses explicitly on this issue [22], authors like Duarte et al [11] and Pulice et al [23] have expressed the need for further exploration to respond to the numerous crucial questions about ways to ensure the equal distribution of the benefits and costs of hydropower energy. Dongnan et al [24] posit that the implications of long-term benefit sharing should be examined.…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…Engagement with PAPs also reduces the chance for diffusion of impacts through untargetted area support paid directly to governments, for example, in Brazil’s hydropower regulations (Pulice et al, 2019). In those cases, it is not clear that the supposed ‘benefits’ actually do benefit PAPs (ibid)—raising major questions on the project’s justification.…”
Section: Analysis and Conclusionmentioning
confidence: 99%
“…Inclusive Development: Although HDP-2001 envisioned the idea of an inclusive development beyond the borders of urban centers, it lacked a guideline or implementation mechanism for accomplishing the broader vision of "rural poverty reduction" , which is a determining factor for inclusive growth and development (Pulice, Branco, Gallardo, Roquetti, & Moretto, 2019). For instance, failure to adopt the concept of the Local Benefit Sharing Mechanism of hydropower projects, which was the most significant recommendation of the World Commission of Dams 2000 report, was a missed opportunity.…”
Section: A Swot Analysis Of Nepalese Hydropower Policymentioning
confidence: 99%